The role of South Aceh Regency Women's Empowerment Office for Child Protection and Family Planning (DP3AKB) in preventing underage marriage - Zamharira, Cut; Irma, Ade; Jamilah, Jamilah (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
Underage marriage is vulnerable to have an impact on; divorce, poor quality of human resources, domestic violence (KDRT), maternal mortality, and population explosion. The Office of Women's Empowerment, Child Protection and Family Planning (DP3AKB) of South Aceh Regency is part of supporting the tasks of the regional head (Bupati) through the Regional Secretary (Sekda). Among the powers of DP3AKB South Aceh Regency include family planning services, reproductive health, family economic development, child protection and population control. Responding to the number of underage marriages in South Aceh District, DP3AKB tries to play a role in preventing it, so that the number does not increase. This study aims to reveal what factors are the causes of underage marriage and the role of the Women's Empowerment Agency for Child Protection and Family Planning (DP3AKB) South Aceh Regency in preventing underage marriage. Through qualitative descriptive methods, with data collection techniques of observation, interviews and documentation, which were then analyzed, the researchers found four factors causing the occurrence of underage marriages in South Aceh District. Among them are; economic factors, promiscuity, self-desire, and the lack of parental roles. DP3AKB South Aceh Regency in an effort to prevent underage marriages, has carried out a number of activities both through the implementation of counseling in the form of the Linto (husband) and Darabaro (wife) Candidate (Calinda) debriefing program and socialization in the form of the Youth Counseling Information Center (PIK-Remaja) delivered at schools and public environment.